Microsoft Access for the Analysis of Open-ended Responses in Questionnaires and Interviews - Meyer, Thorsten; Gruppe, Harald; Franz, Michael (Forum, qualitative social research, 2002)
Structured interviews or questionnaires often comprise open-ended questions, especially to obtain additional information from the interviewee not covered by standardised questions. Ordinarily, the analysis of these open-ended questions cannot be undertaken by the same computer program, in which quantitative data is entered and managed, which impedes the combination of open-ended and closed answer formats. The usage of the database management program Microsoft Access is widespread. It allows for various ways of entering quantitative data, of data management and data export. The entry of text material is convenient and almost unrestricted due to memo-format variables. Given the possibility to manage quantitative and qualitative data with the same computer software, we tried to use the programming properties of MS Access (Visual Basic with MS-Access-supplements) for the purpose of content analysis. The present paper comprises a description of the construction of data tables, queries, code lists and data entry forms. In addition, the construction of coding units (paraphrasing of text data), the coding process and the restructuring for subsequent statistical analysis is illustrated. In addition, the export of data into the statistical software package SPSS and the analysis of inter-coder reliability are discussed. This is based on the data collected from open-ended quality of life interviews with chronic schizophrenic persons and a paper-pencil assessment of patient satisfaction during a psychiatric hospital stay. URN: urn:nbn:de:0114-fqs0202206